Return on investment? Associations between resources and effectiveness of player development in a male rugby union talent system - Shelley, A.; MacNamara, Á.; Taylor, J.; Scriney, M.; McCarthy, N.; Jones, B.; Behan, S. (Journal of Science and Medicine in Sport, 2026)
Objectives Substantial research has considered the factors contributing to effective talent systems, including environmental features and resources. This study aimed to quantitatively explore associations between academy resources and outcome effectiveness in the English male Premiership rugby talent system.